MAVS-mediated apoptosis and its inhibition by viral proteins. - Yu Lei (Public Library of Science (PLoS), 2009)
Background Host responses to viral infection include both immune activation and programmed cell death. The mitochondrial antiviral signaling adaptor, MAVS (IPS-1, VISA or Cardif) is critical for host defenses to viral infection by inducing type-1 interferons (IFN-I), however its role in virus-induced apoptotic responses has not been elucidated. Principal findings We show that MAVS causes apoptosis independent of its function in initiating IFN-I production. MAVS-induced cell death requires mitochondrial localization, is caspase dependent, and displays hallmarks of apoptosis. Furthermore, MAVS(-/-) fibroblasts are resistant to Sendai virus-induced apoptosis. A functional screen identifies the hepatitis C virus NS3/4A and the Severe Acute Respiratory Syndrome coronavirus (SARS-CoV) nonstructural protein (NSP15) as inhibitors of MAVS-induced apoptosis, possibly as a method of immune evasion. Significance This study describes a novel role for MAVS in controlling viral infections through the induction of apoptosis, and identifies viral proteins which inhibit this host response.